Ultra-low VOCs light fiberboard added with transition metal oxide / expanded perlite composite filler and preparation method of ultra-low VOCs light fiberboard

By using transition metal oxide/expanded perlite composite filler in fiberboard, ultra-low VOCs and formaldehyde release of fiberboard are achieved, along with lightweighting and continuous purification functions. This solves the VOCs and formaldehyde release problems existing in the prior art, and the process is simple and easy to industrialize.

CN121018723APending Publication Date: 2025-11-28GUANGXI ACAD OF SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511562887.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing fiberboard has problems with the release of volatile organic compounds (VOCs) and formaldehyde during use. Existing solutions such as formaldehyde-free adhesives are costly, physical adsorbents pose a risk of secondary release, and expanded perlite has limited functionality and cannot effectively solve this problem.

Method used

By using a transition metal oxide/expanded perlite composite filler, transition metal oxides (such as MnO2, Co3O4, CeO2) are loaded onto the surface of expanded perlite, combined with a three-stage hot pressing process, synergistic purification through physical adsorption and chemical catalytic degradation is achieved, thus preparing ultra-low VOCs lightweight fiberboard.

Benefits of technology

It achieves ultra-low VOCs and formaldehyde release in fiberboard, making the board lightweight, eliminating the risk of secondary release, providing continuous air purification, and possessing good mechanical properties. The process is simple and easy to scale up.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121018723A_ABST
    Figure CN121018723A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of artificial boards, and discloses an ultralow VOCs light fiberboard added with transition metal oxide / expanded perlite composite filler and a preparation method of the ultralow VOCs light fiberboard. The composite filler is formed by loading transition metal oxides (MnO2, Co3O4, CeO2 and the like) on expanded perlite (EP). The preparation method comprises the following steps: dipping acid-washed and activated EP in a transition metal salt solution, and drying and calcining to obtain a modified product (M-EP). The M-EP filler is mixed with wood fibers and an adhesive according to the proportion of 5-20 wt%, and the fiberboard is prepared through the processes of paving, pre-pressing and hot pressing. Through the synergistic effect of physical adsorption and chemical catalytic degradation, the VOCs and formaldehyde emission of the fiberboard is remarkably reduced, and the fiberboard is endowed with the capability of continuously purifying free formaldehyde in air. Meanwhile, the density of the board is effectively reduced through introduction of EP, the light-weight and functional integrated design of the board is achieved, and the board is suitable for the fields of furniture manufacturing and indoor decoration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of engineered wood products technology, and specifically relates to an ultra-low VOCs lightweight fiberboard with added transition metal oxide / expanded perlite composite filler and its preparation method. Background Technology

[0002] Fiberboard, as one of the "three major boards" (plywood, fiberboard, and particleboard), boasts excellent flatness, mechanical strength, and processability, making it widely used in furniture manufacturing, packaging, construction, and other fields. Furthermore, compared to other boards, fiberboard, due to its manufacturing process characteristics, is the easiest engineered wood product to achieve lightweight, heat insulation, flame retardancy, and sound insulation properties. Therefore, fiberboard continues to hold an indispensable and important position in the engineered wood product industry.

[0003] However, due to the nature of wood itself and the use of aldehyde-based adhesives, fiberboard has fatal drawbacks such as the release of volatile organic compounds (VOCs), formaldehyde, and unpleasant odors. To reduce VOCs and formaldehyde release from fiberboard, three main approaches are used: first, using formaldehyde-free adhesives (such as isocyanate MDI), but these are expensive and require stringent production processes; second, adding physical adsorption VOCs or formaldehyde scavengers (such as ammonia, urea, and carbon-based adsorbents), but these materials can only adsorb, not decompose, VOCs and formaldehyde, posing a risk of secondary release after adsorption saturation; and third, post-processing the finished product (such as veneer or photocatalyst coating), but this method increases process complexity and the surface functional layer is prone to wear and failure.

[0004] To address this challenge, the industry currently employs the following main technological approaches: First, using formaldehyde-free adhesives: for example, replacing traditional aldehyde-based adhesives with isocyanates (MDI). While this method avoids formaldehyde introduction at the source, formaldehyde-free adhesives like MDI are extremely expensive and require specific production line equipment and processes, significantly increasing production costs and raising the technological barrier, making large-scale adoption difficult. Second, adding physical adsorbents: adding substances such as ammonia, urea, activated carbon, or porous mineral materials to the slab to capture VOCs and formaldehyde molecules through physical or chemical adsorption. However, these methods essentially only "transfer" and "temporarily store" pollutants, failing to achieve fundamental degradation. Once the adsorption sites become saturated, or under changes in ambient temperature and humidity, the adsorbed pollutants risk being released back into the air, leading to "secondary pollution."

[0005] On the other hand, seeking a functional additive that combines low cost, high porosity, good stability, and easy uniform dispersion within fiberboard is another research direction for achieving lightweight and functional fiberboard. For example, expanded perlite, as a natural, inexpensive, lightweight porous material, has extremely low bulk density and a certain specific surface area, and theoretically can be used as a lightweight filler. However, expanded perlite alone has a limited function, and its physical structure and chemical properties make it difficult to effectively solve the core pollution problem of continuous VOCs / formaldehyde release from fiberboard.

[0006] Therefore, developing a fiberboard that combines ultra-low VOCs release, continuous air purification, and lightweight characteristics is of great significance for addressing industry pain points and increasing product added value. Summary of the Invention

[0007] The primary objective of this invention is to provide a transition metal oxide / expanded perlite composite filler (M-EP) that combines physical adsorption and chemical catalytic degradation functions.

[0008] Another objective of this invention is to provide a method for preparing the above-mentioned composite filler, which is simple in process, mild in conditions, and easy to scale up for production.

[0009] Another objective of this invention is to provide a method for preparing lightweight fiberboard with ultra-low VOCs emission, air purification function, and low density using the above-mentioned M-EP filler.

[0010] The ultimate objective of this invention is to provide a lightweight fiberboard produced by the above method and its applications.

[0011] To achieve the above objectives, the technical solution adopted by the present invention is as follows.

[0012] An ultra-low VOCs lightweight fiberboard with added transition metal oxide / expanded perlite composite filler is prepared from the following raw materials in parts by weight: 100 parts wood fiber, 8-15 parts adhesive, and 5-20 parts composite filler; wherein the composite filler uses expanded perlite as a carrier, and the surface and pores of the carrier are loaded with transition metal oxide active components; wherein the transition metal oxide is selected from any one or more of MnO2, Co3O4, and CeO2.

[0013] In this invention, further, based on the total mass of the composite filler, the loading of the transition metal oxide is 3.0-15.0 wt%; the transition metal oxide is in the form of nanoparticles.

[0014] Furthermore, in this invention, the method for preparing the composite filler includes the following steps.

[0015] S1. The expanded perlite is acid-washed and activated, then washed with water until neutral and dried to obtain activated expanded perlite.

[0016] S2. The activated expanded perlite is immersed in a transition metal salt solution and stirred.

[0017] S3. The material impregnated in step S2 is subjected to solid-liquid separation. The resulting solid is then dried and calcined to obtain the composite filler.

[0018] In this invention, further, in step S1, the acid solution used for pickling activation is a hydrochloric acid, sulfuric acid or nitric acid solution with a concentration of 0.5~2.0 mol / L, and the pickling activation time is 1.0~3.0 h.

[0019] In this invention, further, in step S2, the transition metal salt solution is an aqueous solution of any one or more of permanganate, manganese nitrate, manganese acetate, cobalt nitrate, and cerium nitrate, with a concentration of 0.2 to 3.0 mol / L; the immersion time is 2.0 to 6.0 h.

[0020] In this invention, further, in step S3, the drying temperature is 80 ~ 120 ℃ and the time is 6 ~ 12 h; the calcination is carried out in an air atmosphere, the calcination temperature is 300 ~ 500 ℃ and the calcination time is 2.0 ~ 4.0 h.

[0021] In this invention, the adhesive is further described as urea-formaldehyde resin or melamine-formaldehyde resin.

[0022] The present invention also provides a method for preparing ultra-low VOCs lightweight fiberboard as described above, comprising: mixing wood fibers, adhesives and the composite filler evenly, and then laying, pre-pressing and hot-pressing.

[0023] In this invention, the hot pressing process is further described as a three-stage hot pressing process with the following parameters: high pressure stage: pressure 1.2~1.8 MPa, temperature 200~240 ℃; holding pressure stage: pressure 0.2~0.5 MPa, temperature 175~190 ℃; thickness stage: pressure 1.8~2.4 MPa, temperature 140~180 ℃; and platen speed 5.0~7.5 m / min.

[0024] In summary, due to the adoption of the above technical solutions, the present invention has at least the following beneficial effects.

[0025] 1. This invention creatively constructs a synergistic purification mechanism of "physical adsorption-surface concentration-catalytic oxidation". First, utilizing the well-developed porous structure of expanded perlite, VOCs (including formaldehyde) molecules released during the manufacturing and use of fiberboard are efficiently captured and enriched. Subsequently, transition metal oxides firmly loaded on the surface and within the pores of the carrier serve as active sites. Under the excitation of the heat energy (150~240℃) provided during the hot pressing stage of the fiberboard, the enriched organic pollutants are completely catalytically oxidized into harmless carbon dioxide and water. This process achieves a qualitative change from "temporary adsorption" to "permanent degradation", not only enabling the board itself to meet ultra-low VOCs release standards, but also endowing it with the ability to continuously purify formaldehyde from the surrounding environment, without the risk of secondary release, and with long-lasting and stable function.

[0026] 2. This invention utilizes the extremely low bulk density of expanded perlite (approximately 40~120 kg / m³). 3 While partially replacing wood fiber, it significantly reduces the density of the final product. Due to the extremely low density of the expanded perlite filler used, the density of the board can be controlled between 450 and 650 kg / m³. 3 Within the lightweight range, the goal of lightweight fiberboard has been successfully achieved, which not only saves raw material costs but also reduces logistics and transportation costs. Although inorganic fillers were introduced, by optimizing their addition ratio (5-20 parts), the key mechanical properties of the finished board, such as internal bond strength and static bending strength, are still better than the mandatory requirements of national standards, achieving an excellent balance between lightweight and high strength.

[0027] 3. The composite filler preparation process provided by this invention is simple, operates under mild conditions, and is easy to scale up for production. More importantly, in application, the addition of this filler can be directly integrated into the existing standard production process of fiberboard (mixing-laying-pre-pressing-hot pressing), without requiring major modifications to existing core equipment and processes or additional expensive investments. This high degree of process compatibility greatly lowers the threshold for the promotion and application of this technology in existing industries, resulting in high industrialization feasibility and significant economic benefits. Attached Figure Description

[0028] Figure 1 This is a process flow diagram for the preparation of ultra-low VOCs lightweight fiberboard in Example 1. Detailed Implementation

[0029] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0030] Example 1.

[0031] 1. Preparation of transition metal oxide / expanded perlite composite filler.

[0032] (1) Pretreatment: Grind the expanded perlite particles, pass them through a 150-mesh sieve, soak them in a 0.5 mol / L dilute hydrochloric acid solution for 1.0 h, wash them with deionized water until neutral, and dry them for later use.

[0033] (2) Impregnation: Prepare a cobalt nitrate solution with a concentration of 1.0 mol / L, and immerse the expanded perlite pretreated in step (1) into it and stir at room temperature for 3.0 h.

[0034] (3) Drying and calcination: The impregnated mixture was filtered and separated. The solid product was dried at 110 °C for 12.0 h, and then calcined in air at 500 °C for 3.0 h. After cooling, it was ground to obtain the Co3O4 / expanded perlite composite filler.

[0035] 2. Preparation of ultra-low VOCs lightweight fiberboard.

[0036] 1) Material mixing: Place the dried wood fiber, urea-formaldehyde adhesive and Co3O4 / expanded perlite composite filler in a mixer and mix thoroughly in a weight ratio of 100:12:8.

[0037] 2) Slab laying and pre-compression: The mixture is laid into a uniform slab, and then cold pre-compressed at a pressure of 2.0 MPa for 2.0 min.

[0038] 3) Hot pressing: The pre-pressed slab is fed into a hot press and formed using a three-stage hot pressing process: a high-pressure stage, a holding-pressure stage, and a thickness-fixing stage. The high-pressure stage has a pressure of 1.4 MPa and a temperature of 230 ℃; the holding-pressure stage has a pressure of 0.3 MPa and a temperature of 180 ℃; and the thickness-fixing stage has a pressure of 2.0 MPa and a temperature of 150 ℃. The pressing speed is 6.0 m / min. After hot pressing, the slab is cooled, trimmed, and sanded to obtain the ultra-low VOCs lightweight fiberboard. The process flow diagram is shown below. Figure 1 As shown.

[0039] Example 2

[0040] 1. Preparation of transition metal oxide / expanded perlite composite filler.

[0041] (1) Pretreatment: Grind the expanded perlite particles, pass them through a 180-mesh sieve, soak them in a 1.5 mol / L dilute hydrochloric acid solution for 1.0 h, wash them with deionized water until neutral, and dry them for later use.

[0042] (2) Impregnation: Prepare a 2.5 mol / L cerium nitrate solution and immerse the expanded perlite pretreated in step (1) into it and stir at room temperature for 5.0 h.

[0043] (3) Drying and calcination: The impregnated mixture was filtered and separated. The solid product was dried at 105 °C for 12.0 h, and then calcined in air at 450 °C for 4.0 h. After cooling, it was ground to obtain the CeO2 / expanded perlite composite filler.

[0044] 2. Preparation of ultra-low VOCs lightweight fiberboard.

[0045] 1) Material mixing: Place the dried wood fiber, melamine-formaldehyde resin adhesive and CeO2 / expanded perlite composite filler in a mixer at a weight ratio of 100:10:12 and mix thoroughly.

[0046] 2) Slab laying and pre-compression: The mixture is laid into a uniform slab, and then cold pre-compressed at a pressure of 2.0 MPa for 2.0 min.

[0047] 3) Hot pressing: The pre-pressed slab is fed into a hot press and formed using a three-stage hot pressing process: a high-pressure stage, a holding-pressure stage, and a thickness-fixing stage. The high-pressure stage has a pressure of 1.8 MPa and a temperature of 210 ℃; the holding-pressure stage has a pressure of 0.3 MPa and a temperature of 190 ℃; and the thickness-fixing stage has a pressure of 1.8 MPa and a temperature of 170 ℃. The pressing speed is 6.0 m / min. After hot pressing, the slab is cooled, trimmed, and sanded to obtain the ultra-low VOCs lightweight fiberboard.

[0048] Example 3

[0049] 1. Preparation of transition metal oxide / expanded perlite composite filler.

[0050] (1) Pretreatment: Grind the expanded perlite particles, pass them through a 200-mesh sieve, soak them in a 1.0 mol / L dilute sulfuric acid solution for 1.5 h, wash them with deionized water until neutral, and dry them for later use.

[0051] (2) Impregnation: Prepare a 1.0 mol / L manganese nitrate solution and immerse the pretreated expanded perlite from step (1) into it and stir at room temperature for 4.0 h.

[0052] (3) Drying and calcination: The impregnated mixture was filtered and separated. The solid product was dried at 120 °C for 8.0 h, and then calcined in air at 400 °C for 2.0 h. After cooling, it was ground to obtain the MnO2 / expanded perlite composite filler.

[0053] 2. Preparation of ultra-low VOCs lightweight fiberboard.

[0054] 1) Material mixing: Place the dried wood fiber, urea-formaldehyde adhesive and MnO2 / expanded perlite composite filler in a mixer and mix thoroughly in a ratio of 100:15:10 by weight.

[0055] 2) Slab laying and pre-pressing: The mixture is laid into a uniform slab and then cold pre-pressed at a pressure of 2.5 MPa for 1.5 min.

[0056] 3) Hot pressing: The pre-pressed slab is fed into a hot press and formed using a three-stage hot pressing process: a high-pressure stage, a holding-pressure stage, and a thickness-fixing stage. The high-pressure stage has a pressure of 1.5 MPa and a temperature of 220 ℃; the holding-pressure stage has a pressure of 0.4 MPa and a temperature of 175 ℃; and the thickness-fixing stage has a pressure of 1.9 MPa and a temperature of 165 ℃. The pressing speed is 6.5 m / min. After hot pressing, the slab is cooled, trimmed, and sanded to obtain the ultra-low VOCs lightweight fiberboard.

[0057] Example 4

[0058] 1. Preparation of transition metal oxide / expanded perlite composite filler.

[0059] (1) Pretreatment: Grind the expanded perlite particles, pass them through a 200-mesh sieve, soak them in a 2.0 mol / L dilute hydrochloric acid solution for 1.0 h, wash them with deionized water until neutral, and dry them for later use.

[0060] (2) Impregnation: Prepare a manganese acetate solution with a concentration of 1.8 mol / L, and immerse the expanded perlite pretreated in step (1) into it and stir at room temperature for 3.5 h.

[0061] (3) Drying and calcination: The impregnated mixture was filtered and separated. The solid product was dried at 110 °C for 10.0 h, and then calcined in air at 450 °C for 3.0 h. After cooling, it was ground to obtain the MnO2 / expanded perlite composite filler.

[0062] 2. Preparation of ultra-low VOCs lightweight fiberboard.

[0063] 1) Material mixing: Place the dried wood fiber, urea-formaldehyde adhesive and MnO2 / expanded perlite composite filler in a mixer and mix thoroughly in a weight ratio of 100:15:18.

[0064] 2) Slab laying and pre-pressing: The mixture is laid into a uniform slab and then cold pre-pressed at a pressure of 2.5 MPa for 1.5 min.

[0065] 3) Hot pressing: The pre-pressed slab is fed into a hot press and formed using a three-stage hot pressing process: a high-pressure stage, a holding-pressure stage, and a thickness-fixing stage. The high-pressure stage has a pressure of 1.6 MPa and a temperature of 230 ℃; the holding-pressure stage has a pressure of 0.3 MPa and a temperature of 190 ℃; and the thickness-fixing stage has a pressure of 2.2 MPa and a temperature of 165 ℃. The pressing speed is 7.0 m / min. After hot pressing, the slab is cooled, trimmed, and sanded to obtain the ultra-low VOCs lightweight fiberboard.

[0066] Comparative Example 1.

[0067] Comparative Example 1 is the same as Example 1, except that Comparative Example 1 does not add transition metal oxide / expanded perlite composite filler.

[0068] Comparative Example 2.

[0069] Comparative Example 2 is the same as Example 1, except that the composite filler is replaced with an equal weight of expanded perlite powder without loaded transition metal oxides.

[0070] Comparative Example 3.

[0071] Comparative Example 3 is the same as Example 1, except that the Co3O4 / expanded perlite composite filler is replaced with an equimolar amount of pure Co3O4 powder (i.e., no expanded perlite carrier is used).

[0072] Experiment and results analysis.

[0073] 1. Testing methods.

[0074] VOCs emission testing and grading: The test is conducted according to GB / T29899-2024 "Test Method for Emission of Volatile Organic Compounds from Wood-based Panels and Their Products - Small Release Chamber Method", and the grading is carried out according to GB / T44690-2024 "Classification of Emission of Volatile Organic Compounds from Wood-based Panels and Their Products".

[0075] Mechanical properties: Physical and chemical properties were tested according to GB / T17657-2022 "Test methods for physical and chemical properties of wood-based panels and decorative panels".

[0076] Formaldehyde emission: Formaldehyde emission was tested according to GB / T39600-2021 "Classification of Formaldehyde Emission of Wood-based Panels and Their Products".

[0077] Porosity P test: P = (1 - ρ0 / ρ) × 100%, where ρ0 is the density of the fiberboard in its natural state; ρ is the density of the fiberboard in its compacted state.

[0078] 2. Test results.

[0079] The performance test results of the fiberboard obtained in Examples 1-4 and Comparative Examples 1-3 are shown in Table 1. The purpose is to compare and analyze the effects of modified expanded perlite powder on the mechanical properties, density, structure, formaldehyde and VOC content of the fiberboard.

[0080]

[0081] Table 1 shows that with the addition of transition metal oxide / expanded perlite powder, fiberboard with ultra-low VOCs and formaldehyde content can be obtained. Comparative Example 1 and Example 1 show that the formaldehyde content and VOCs content of ordinary fiberboard are 0.0507 mg / m³. 3 and 642.7 μg / m 3 However, after adding transition metal oxide / expanded perlite powder, the aldehyde content and VOCs content of the fiberboard prepared in Example 1 decreased to 0.0091 mg / m³. 3 and 78.8 μg / m 3 This is because expanded perlite has a rich porous structure, which first enriches VOCs and formaldehyde molecules through physical adsorption. Subsequently, the transition metal oxides loaded on it can catalytically decompose VOCs and formaldehyde into CO2 and H2O at a temperature of 150 ~ 240 ℃ during fiberboard pressing, achieving a synergistic effect of "adsorption-concentration-catalytic degradation", resulting in extremely low VOCs and formaldehyde release from the board.

[0082] The fiberboard prepared in Examples 1-4 and Comparative Example 2 had a density of approximately 588-627 kg / m³. 3 The densities of Comparative Examples 1 and 3, without the addition of expanded perlite, were 805–883 kg / m³. 3 This demonstrates that the addition of expanded perlite powder can significantly reduce the density of fiberboard, increase its porosity, and achieve its lightweight nature. Although the mechanical properties of the fiberboard prepared in Examples 1-4 and Comparative Examples 2, such as internal bond strength and static bending strength, are somewhat reduced, this is because perlite is an inorganic brittle material whose softness, toughness, and tensile properties are not as good as wood fiber. However, as long as its addition amount is controlled to be less than 20%, the overall mechanical properties of the prepared fiberboard are better than the national standard requirements.

[0083] Finally, it should be noted that the above embodiments are only used to describe preferred embodiments of the present invention, and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the embodiments, those skilled in the art should understand that various modifications and improvements made to the technical solutions of the present invention by means of modifications or equivalent substitutions are all within the scope of protection claimed by the present invention.

Claims

1. A lightweight fiberboard with ultra-low VOCs and added transition metal oxide / expanded perlite composite filler, characterized in that, It is prepared from the following raw materials in parts by weight: 100 parts wood fiber, 8-15 parts adhesive, and 5-20 parts composite filler; the composite filler uses expanded perlite as a carrier, and the surface and pores of the carrier are loaded with transition metal oxide active components; the transition metal oxide is selected from any one or more of MnO2, Co3O4, and CeO2.

2. The lightweight fiberboard according to claim 1, characterized in that, Based on the total mass of the composite filler, the loading of the transition metal oxide is 3.0-15.0 wt%; the transition metal oxide is in the form of nanoparticles.

3. The lightweight fiberboard according to claim 1, characterized in that, The method for preparing the composite filler includes the following steps: S1. The expanded perlite is acid-washed and activated, then washed with water until neutral and dried to obtain activated expanded perlite; S2. The activated expanded perlite is impregnated in a transition metal salt solution and stirred; S3. The material impregnated in step S2 is subjected to solid-liquid separation. The resulting solid is then dried and calcined to obtain the composite filler.

4. The lightweight fiberboard according to claim 3, characterized in that, In step S1, the acid solution used for pickling and activation is a hydrochloric acid, sulfuric acid, or nitric acid solution with a concentration of 0.5~2.0 mol / L, and the pickling and activation time is 1.0~3.0 h.

5. The lightweight fiberboard according to claim 3, characterized in that, In step S2, the transition metal salt solution is an aqueous solution of any one or more of permanganate, manganese nitrate, manganese acetate, cobalt nitrate, and cerium nitrate, with a concentration of 0.2 to 3.0 mol / L; the immersion time is 2.0 to 6.0 h.

6. The lightweight fiberboard according to claim 3, characterized in that, In step S3, the drying temperature is 80~120℃ and the time is 6~12 h; the calcination is carried out in an air atmosphere, the calcination temperature is 300~500℃ and the calcination time is 2.0~4.0 h.

7. The lightweight fiberboard according to claim 1, characterized in that, The adhesive is urea-formaldehyde resin or melamine-formaldehyde resin.

8. A method for preparing a lightweight fiberboard as described in any one of claims 1-7, characterized in that, include: Wood fibers, adhesives, and the composite filler are mixed evenly, and then laid, pre-pressed, and hot-pressed into shape.

9. The method according to claim 8, characterized in that, The hot pressing process employs a three-stage hot pressing technique, with the following process parameters: High-pressure section: pressure 1.2~1.8 MPa, temperature 200~240 ℃; Pressure holding section: pressure 0.2~0.5 MPa, temperature 175~190 ℃; Fixed thickness section: pressure 1.8~2.4 MPa, temperature 140~180 ℃; The platen speed is 5.0~7.5 m / min.

Citation Information

Patent Citations

  • Preparation method of expanded perlite loaded nanometer TiO2 compound photocatalysis material

    CN102698759A

  • Expanded perlite low-density composite shaving board and manufacturing method thereof

    CN103624859A

  • Ultra-light-weight composite environment-friendly fiber board and preparing method of ultra-light-weight composite environment-friendly fiber board

    CN105064603A

  • Preparation method of modified nanometer catalyst for absorbing pollutants

    CN106111165A

  • VOCs catalytic combustion catalyst and preparation method thereof

    CN110124645A